2020
DOI: 10.1186/s12916-020-01766-9
|View full text |Cite
|
Sign up to set email alerts
|

External validation of prognostic models predicting pre-eclampsia: individual participant data meta-analysis

Abstract: Background Pre-eclampsia is a leading cause of maternal and perinatal mortality and morbidity. Early identification of women at risk during pregnancy is required to plan management. Although there are many published prediction models for pre-eclampsia, few have been validated in external data. Our objective was to externally validate published prediction models for pre-eclampsia using individual participant data (IPD) from UK studies, to evaluate whether any of the models can accurately predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…It is important to highlight that, although it was not the aim of this study, combined prediction models have shown moderate predictive performance, with important limitations such as heterogeneity of the populations studied, low reproducibility of the methods used (mainly uterine artery Doppler), and a substantial lack of external validation. Evidence to support the use of these PE prediction models in clinical decision-making is limited and their predictive performance must be examined and validated locally before they can be considered for use in clinical practice ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that, although it was not the aim of this study, combined prediction models have shown moderate predictive performance, with important limitations such as heterogeneity of the populations studied, low reproducibility of the methods used (mainly uterine artery Doppler), and a substantial lack of external validation. Evidence to support the use of these PE prediction models in clinical decision-making is limited and their predictive performance must be examined and validated locally before they can be considered for use in clinical practice ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 In this regard, alternative predictive tools have been designed to improve the accuracy of diagnosis of the severity of preeclampsia. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…10 In this regard, alternative predictive tools have been designed to improve the accuracy of diagnosis of the severity of preeclampsia. 11,12 Our study was focused on hypertensive pregnancies immediately before delivery that corresponds well with those without routine prenatal visits during the pandemic. In order to adapt to the recent change in ACOG treatment guidelines and the wavering blood pressure or proteinuria accuracy, we aimed to use an efficient alternative method of combining maternal-obstetrical characteristics (MOCs) and complete blood cell counts (CBCs) with different red blood cell (RBC) indices 13 to evaluate and further confirm PE severity immediately.…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 7 Calibration plots for models predicting any-onset pre-eclampsia using first-trimester clinical characteristics and biochemical markers in data sets with > 100 outcome events. (a) Model 4115 in POP; 161 (b) model 5 128 in POP; 161 (c) model 6147 in St George's; 163 and (d) model 6147 in POP.161 Reproduced from Snell et al52 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material.…”
mentioning
confidence: 99%
“…This figure contains information from several sources 115,147,[229][230][231][232][233][234][235][236]238 Reproduced from Snell et al52 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material.…”
mentioning
confidence: 99%